Cooperativismo e inclusão social: um olhar sobre a realidade da cooperativa social de pais, amigos e portadores de deficiência (coepad). - Lopes, Marinalva da Silva (Universidade Federal do Tocantins, 2023)
Cooperativism greatly influences social inclusion, even though there are few “Special” cooperatives in the Production of Goods and Services branch. COEPAD (Social Cooperative of Parents, Friends and People with Disabilities) was the first cooperative organization of the special branch created in Brazil, founded in 1999 with the purpose of inclusion and training of people with special needs. Through this, it is worth emphasizing that the reference clearly addresses insertion into the labor market, having as a mechanism the cooperative doctrine, its values and principles, in accordance with laws and decrees that govern and help citizens with special needs. The present work is methodologically characterized as bibliographical, qualitative and exploratory and adopted the case study method. Thus, the main results reveal that the creation of more special cooperatives can be one of the possible solutions to reduce problems related to social inclusion, as this will encourage the generation of jobs and, consequently, social inclusion wherever the organization is located.